2010
DOI: 10.1016/j.trstmh.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the dynamics of the clinical and immunological evolution of human Leishmania (L.) infantum chagasi infection in the Brazilian Amazon region

Abstract: This prospective study was carried out from October 2003 to December 2005 and involved a cohort of 946 individuals of both genders, aged 1-89 years, from an endemic area for American visceral leishmaniasis (AVL), in Pará State, Brazil. The aim of the study was to analyze the dynamics of the clinical and immunological evolution of human Leishmania (L.) infantum chagasi infection represented by the following clinical-immunological profiles: asymptomatic infection (AI); symptomatic infection (SI=AVL); subclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
34
1
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 21 publications
13
34
1
17
Order By: Relevance
“…VL patients' clinical manifestations and laboratory abnormalities permit the diagnosis of the most severe cases and cases at greater risk of disease progression 8,17,18 . Our clinical and laboratory fi ndings agree with those reported by previous studies, as a combination of fever, hepatosplenomegaly, anemia, and leukopenia was frequently observed and led to the suspicion of VL in such cases, particularly in children 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VL patients' clinical manifestations and laboratory abnormalities permit the diagnosis of the most severe cases and cases at greater risk of disease progression 8,17,18 . Our clinical and laboratory fi ndings agree with those reported by previous studies, as a combination of fever, hepatosplenomegaly, anemia, and leukopenia was frequently observed and led to the suspicion of VL in such cases, particularly in children 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that there is no dichotomy in the production of cytokines in VL, but rather a predominance of elevated levels of a pool of cytokines 17,18,24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, VL is characterized by splenomegaly, hepatomegaly, fever, and pancytopenia. 78,79 Tegumentary leishmaniasis presents distinct forms and the main ones are as follows: 1) localized cutaneous leishmaniasis, characterized by a simple or multiple ulcer, can be caused by all dermotropic Leishmania species; 2) disseminated cutaneous leishmaniasis, characterized by multiple small ulcers; 3) diffuse cutaneous leishmaniasis is the anergic form of TL, characterized by multiple nodules or papules, generally presenting no ulceration; 4) mucosal leishmaniasis is mainly characterized by nasal involvement, presenting perforation or ulceration, which can also involve the palate and pharynx. 12 The spreading of HIV infection to rural areas and the urbanization of leishmaniasis has influenced the clinical progression and diagnosis of leishmaniasis.…”
Section: Leishmaniasismentioning
confidence: 99%
“…We designed the current study in a similar manner as 28 our two previous studies; one has already been published 29 and the other was accepted for publication .…”
Section: Population and Study Designmentioning
confidence: 99%